2018
DOI: 10.1007/978-3-319-99130-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Random Additive Control Flow Error Detection

Abstract: Today, embedded systems are being used in many (safetycritical) applications. However, due to their decreasing feature size and supply voltage, such systems are more susceptible to external disturbances such as electromagnetic interference. These external disturbances are able to introduce bit-flips inside the microcontroller's hardware. In turn, these bit-flips may also corrupt the software. A possible software corruption is a control flow error. This paper proposes a new softwareimplemented control flow erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…The shown UML class diagram depicts the classes and methods to implement a CFE detection technique. Our plugin supports the following CFE detection techniques: CFCSS [18], YACCA (2 versions) [10], ECCA [1], RSCFC [16], SEDSR [5], SCFC [6], SIED [17], RASM [21] and RACFED [22]. However, to keep the diagram in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The shown UML class diagram depicts the classes and methods to implement a CFE detection technique. Our plugin supports the following CFE detection techniques: CFCSS [18], YACCA (2 versions) [10], ECCA [1], RSCFC [16], SEDSR [5], SCFC [6], SIED [17], RASM [21] and RACFED [22]. However, to keep the diagram in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…When doing this however, and taking the appropriate measures to assure the compiler does not optimize away the added instructions, experiments have shown that the CFE detection techniques detect around 65 % of the occurring CFEs. In contrast, literature describes an error detection ratio of 75 % and higher [18,10,1,16,5,6,17,21,22]. This mismatch in error detection ratios is caused by the fact that human-readable high-level code is not mapped one-to-one to machine-readable low-level code.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…To increase the reliability of embedded systems, several software-implemented CFE detection techniques, have been proposed [10,11]. In a previous comparative study, we developed a CFE detection technique called RACFED which has a higher detection ratio at a lower execution time overhead when compared to similar techniques [15]. The imposed execution time overhead, however, is still relatively high.…”
Section: Introductionmentioning
confidence: 99%